Pemanfaatan E-Office dalam Upaya Meningkatkan Kinerja Pegawai Desa Cicalengka Kabupaten Tangerang - Widowati Widowati; Santi Octavianti; Hasudungan Pangaribuan (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The community service activity aimed to enhance the administrative performance of village employees through the utilization of E-Office technology in Cicalengka Village, Tangerang Regency. This program was initiated to address the challenges faced by village administrations that still relied on conventional and manual systems, which often hindered efficiency and transparency. The purpose of the activity was to improve employees’ understanding and skills in using digital office applications to support effective governance. The PKM was conducted on November 2, 2025, in Cicalengka Village by three lecturers from Universitas Pamulang, involving fifteen village officials as participants. The implementation consisted of three stages: preparation, execution, and reporting. The execution stage included material presentation, hands-on practice, discussion, and question-and-answer sessions. The results showed significant improvement in participants’ knowledge and ability to operate E-Office applications, leading to more efficient document management and communication within the village administration. Furthermore, participants expressed strong enthusiasm to integrate E-Office systems into their daily work processes. This program successfully contributed to strengthening digital-based governance at the village level.